2015
DOI: 10.1111/pbr.12295
|View full text |Cite
|
Sign up to set email alerts
|

Sources of resistance to Indian pathotypes of Puccinia graminis tritici and P. triticina in durum wheat

Abstract: Stem rust and leaf rust are important diseases affecting durum wheat production in India. Inheritance and extent of diversity in resistance were studied in five durum genotypes, viz. ʽB 662', ʽED 2398-A', ʽHG 110', ʽIWP 5019' and ʽLine 1172ʼ using Pgt pathotypes 40A and 117-6, and Pt pathotypes 12-2 and 104-2. F 2 and F 3 analyses showed that resistance was conferred by one or two genes in each line. In all, four genes for resistance to 40A, and eight each for pathotypes 117-6 and 12-2 were identified among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
2
0
2
Order By: Relevance
“…This study revealed that resistance in each of the four cultivars against the Pgt pathotypes 15-1 and 40-3 is controlled by a single dominant or two independent dominant genes. The rust resistance in wheat being controlled by one or two genes was reported in many studies (Zia Ul Qamar et al 2009;Olivera et al 2012;Mishra et al 2015). There is commonness for at least one Sr gene conferring resistance against the two test pathotypes between HI 8737 and HI 8713. genes among HI 8498 and HI 8663 are diverse.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This study revealed that resistance in each of the four cultivars against the Pgt pathotypes 15-1 and 40-3 is controlled by a single dominant or two independent dominant genes. The rust resistance in wheat being controlled by one or two genes was reported in many studies (Zia Ul Qamar et al 2009;Olivera et al 2012;Mishra et al 2015). There is commonness for at least one Sr gene conferring resistance against the two test pathotypes between HI 8737 and HI 8713. genes among HI 8498 and HI 8663 are diverse.…”
Section: Discussionmentioning
confidence: 94%
“…The in a dew chamber overnight to ensure spore germination and completion of the infection process and then transferred to glass house benches kept at 18 to 25°C. Infection types displayed on the leaves were recorded about 10-15 days after inoculation according to 0 to 4 scale (Mishra et al 2015). The F 3 families were grown from random F 2 plants of susceptible parent x resistant parent (SxR) crosses to confirm the results of F 2 ratios.…”
Section: Methodsmentioning
confidence: 99%
“…В мировой селекции защита посевов от болезней осуществляется путем создания толерантных и устойчивых сортов [10]. Особенно они необходимы в использовании против болезней листовых зерновых культур, так как другие меры борьбы в этом случае непрактичны.…”
Section: материалы и методы исследования / Materials and Methodsunclassified
“…В мировой селекции защита посевов от болезней осуществляется путем создания толерантных и устойчивых сортов (Mishra et al, 2015). Особенно они необходимы в использовании против болезней листовых зерновых культур, так как другие меры борьбы в этом случае непрактичны.…”
Section: Brown Rust (Puccinia Triticina) and Powdery Mildew (Blumeria...unclassified